An Analysis of Hasan Hanafi's Tafsir Method: Hermeneutics as An Interpretative Approach - Hidayati, Endang; Hutagaol, Bahriyan Ar-Rasyid (STKIP Pesisir Selatan, 2025)
The analysis discusses Hasan Hanafi's tafsir method based on hermeneutics as a contextual approach to understanding the Qur'an. Hasan Hanafi, an Egyptian philosopher and theologian, proposes the method al-Manhaj Al-Ijtima'i fi At-Tafsir, which emphasizes the importance of linking the sacred text to contemporary socio-political realities. Hermeneutics is used as a tool to uncover the meaning of the Qur'an contextually, going beyond literal textual understanding, so that interpretation becomes an expression of the interpreter's social commitment to human problems. Hanafi's perspective rejects traditional tafsir that focuses solely on linguistic analysis and authoritative narratives, instead prioritizing interpretation responsive to the dynamic needs of the Muslim community today. The proposed method involves systematic steps, starting from formulating social commitments, inventorying and classifying verses, to connecting the text with empirical realities to produce transformative and applicable interpretations. This study illustrates the relevance of Hasan Hanafi's hermeneutical approach in supporting Qur'anic understanding that adapts to changing times and social needs of the community.